Strategi Strategi Peningkatan Efisiensi Dan Efektivitas Operasi Agrorelasi: Agrorelasi - Fajriani, Nurdani; Kusman, Hardi; Fadli, Fadli; Sjah, Taslim; Budastra, I Ketut (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This research aims to analyze the business development strategy of an agricultural community, namely Agrorelasi, through SWOT analysis. The research method used was descriptive, with primary and secondary data collection. The results showed that Agrorelasi has strengths in large mass numbers, a lot of networking, actors have extensive knowledge and specific expertise, have a lot of collaboration, and commitment to sustainability. The suggested strategy is to integrate network strengths, optimize sustainability commitments and build strategic partnerships. Overall, the research suggests Agrorelations leverage internal strengths, minimize weaknesses with external support, and build cross-sector collaboration to improve efficiency and effectiveness.